The Ultrastructural Studies on Surface Morphology of Cloaca in Laying and Non- Laying White Leghorn Fowl (Gallus gallus domesticus) - Joshi, Hemant (Indian Journal of Veterinary Anatomy, 2020)
The ultrastructural studies on surface morphology of cloacae was conducted on White Leghorn birds. The scanning electron microscopy of the cloaca of laying and non-laying White leghorn bird showed a remarkable difference in their appearance due to their different secretary functions. Coprodeum of Laying bird revealed longitudinal mucosal folds which were not prominent in non-laying birds and had less mucus secretions. The villi developed a characteristic rough shape in urodeum of laying bird. The mucosa of urodeum of Laying bird was not as smooth as in the case of coprodeum, wherein both transverse and longitudinal mucosal folds were observed. In non-laying bird, the urodeum had comparatively smooth and less number of folds than those of laying bird. Observations on proctodeum in Laying bird had revealed the coarse mucosal fold with small microvilli. The proctodeum of non-laying birds had rough mucosal fold associated with protective mechanism.